2018
DOI: 10.1093/ibd/izy017
|View full text |Cite
|
Sign up to set email alerts
|

Salivary Function and Oral Health Problems in Crohn’s Disease Patients

Abstract: Oral and dental complaints are common in CD patients. Xerostomia is correlated with disease activity-associated quality of life and with the number of oral and dental complaints. Changes in salivary function may contribute to reduced oral health in CD patients. 10.1093/ibd/izy017_video1izy017.video15776803023001.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
29
0
3

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 35 publications
2
29
0
3
Order By: Relevance
“…Previous studies have shown a higher prevalence of oral health problems in patients with IBD compared with the normal population. 9,10,13,14,20 The present study also showed that patients with CD have an increased risk for oral health problems, independent of surgical removal of (a part of) the inflamed intestine, suggesting a generally increased susceptibility of patients with CD for oral health problems.…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…Previous studies have shown a higher prevalence of oral health problems in patients with IBD compared with the normal population. 9,10,13,14,20 The present study also showed that patients with CD have an increased risk for oral health problems, independent of surgical removal of (a part of) the inflamed intestine, suggesting a generally increased susceptibility of patients with CD for oral health problems.…”
Section: Discussionsupporting
confidence: 71%
“…Xerostomia is a subjective feeling of a dry mouth and is not necessarily associated with a reduced saliva secretion rate. 13,14 In this study, patients with CD had a significantly higher total XI score compared with those with UC or CC. This is in line with studies on xerostomia in patients with IBD, in which an increased prevalence of dry mouth was found in patients with IBD 27 and in those with active CD.…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…In addition, differences in salivary composition have also been implicated in the perception of dry mouth [ 19 21 ]; the salivary mucin MUC5B retains large amounts of water and contributes to the generation of a hydrophilic gel essential for lubrication of the oral epithelium [ 22 24 ]. Moreover, MUC5B is the main component that determines the viscoelasticity of saliva [ 24 ]. Local variations in the MUC5B concentration have been reported with higher intensity on the hard palate compared with other oral surfaces [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…This indicates a difference in salivary composition in patients with active disease. 15 The aim of this study was to evaluate oral health problems and salivary function and composition in UC patients and its correlation with disease activity. Secondary, we wanted to evaluate the correlation between quality of life and oral health problems in UC patients with active and inactive disease activity.…”
Section: Introductionmentioning
confidence: 99%